1994
DOI: 10.1017/s0022112094000273
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the Kelvin impulse of a transient cavity

Abstract: The Lagally theorem is used to obtain an expression for the Bjerknes force acting on a bubble in terms of the singularities of the fluid velocity potential, defined within the bubble by analytic continuation. This expression is applied to transient cavity collapse in the neighbourhood of boundaries, allowing analytical estimates to be made of the Kelvin impulse of the cavity. The known result for collapse near a horizontal rigid boundary is recovered, and the Kelvin impulse of a cavity collapsing in the neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 12 publications
(23 reference statements)
0
46
0
1
Order By: Relevance
“…The Kelvin impulse can be interpreted as a linear impulse of the bubble if one attributes a virtual mass to the bubble which corresponds to the liquid mass moving around the cavity. Since axial jets are associated with bubble migration in the direction of the jet, it was suggested that their occurrence and direction can be predicted by analysing the Kelvin impulse at the end of the bubble collapse (Blake et al, 1986(Blake et al, , 1987(Blake et al, , 1997Best and Kucera, 1992;Best and Blake, 1994).…”
Section: Kelvin Impulsementioning
confidence: 99%
“…The Kelvin impulse can be interpreted as a linear impulse of the bubble if one attributes a virtual mass to the bubble which corresponds to the liquid mass moving around the cavity. Since axial jets are associated with bubble migration in the direction of the jet, it was suggested that their occurrence and direction can be predicted by analysing the Kelvin impulse at the end of the bubble collapse (Blake et al, 1986(Blake et al, , 1987(Blake et al, , 1997Best and Kucera, 1992;Best and Blake, 1994).…”
Section: Kelvin Impulsementioning
confidence: 99%
“…The Kelvin impulse of a bubble was introduced by Benjamin and Ellis, 26 and was developed by Blake et al 2,10,27 to derive a criterion governing the directions of the migration and re-entrant jet for bubbles. Our simulations will be compared with the Kelvin impulse theory.…”
Section: A Validationsmentioning
confidence: 99%
“…Best and Blake 27 obtained an analytical estimation of the Kelvin impulse of a bubble in the neighborhood of a rigid surface using the Lagally theorem and assuming the bubble to remain spheri-cal throughout its lifetime. In particular the Kelvin impulse at the end of the collapse phase is given as follows:…”
Section: A Validationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicated that such a model may be generally at most 3% in error, for such quantities as the bubble volume, Kelvin impulse, and bubble trajectory toward the boundary. Higher-order approximations were used by Best and Blake [1], again to obtain criteria for the migration of the bubble.…”
Section: Introductionmentioning
confidence: 99%